Transactions in Kinship (University of Hawai'i Press, 2023)
A collection of essays that follows up on "Adoption in Eastern Oceania" by Vern Carroll. Most were presented at a symposium during the First Annual Association for Social Anthropology in Oceania (ASAO) meeting in 1972.